GENDER-FLUID CHARACTERS IN HANS WILHEM'S PICTURE BOOKS (EUFONI: Journal of Language, Literary, and Cultural Studies, 2020)
This essay looks into the picture books of Hans Wilhem’s Bunny Trouble (1985) and Bad, Bad Bunny Trouble (1994), which depict the non-binary gender aspects of the main character, Bunny. The two picture books portray Bunny as a boy who possesses and demonstrates both masculine and feminine characteristics concurrently. This issue criticizes the rigid definition of traditional gender binary that had been inculcated and constructed in the society (Butler, 1990). By paying attention to the narrative and illustrative elements of the picture books, this essay sheds lights on how Bunny and other supporting characters fervently delineate that gender as fluid aspects rather than rigid characteristics that cannot be possessed and demonstrated by the main character and other characters as well.Keywords: gender aspects, gender-fluid character, picture books